2017
DOI: 10.1007/s11010-017-2965-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of asiatic acid in glioblastoma cells under hypoxia

Abstract: Glioblastoma multiforme is the most common and malignant primary brain tumor in adults. Despite current treatment options including surgery followed by radiation and chemotherapy with temozolomide and cisplatin, the median survival rate remains low (<16 months). Combined with increasing drug resistance and the inability of some compounds to cross the blood–brain barrier, novel compounds are being sought for the treatment of this disease. Here, we aimed to examine the pharmacological effect of Asiatic acid (AA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These cancer cells lines presented sensitivity to encapsulated tarin comparable to usual chemotherapeutic drug effects. Concerning glioblastoma, the determined IC 50 for encapsulated tarin (39.36 μg/mL) was equivalent to 65% of cisplatin (29 μg/mL) and 82.2% of temozolide (33.40 μg/mL) inhibition growth effects (Table 2) [37,38]. On the other hand, breast adenocarcinoma cells displayed a less favorable panorama when compared to literature results.…”
Section: Discussionmentioning
confidence: 95%
“…These cancer cells lines presented sensitivity to encapsulated tarin comparable to usual chemotherapeutic drug effects. Concerning glioblastoma, the determined IC 50 for encapsulated tarin (39.36 μg/mL) was equivalent to 65% of cisplatin (29 μg/mL) and 82.2% of temozolide (33.40 μg/mL) inhibition growth effects (Table 2) [37,38]. On the other hand, breast adenocarcinoma cells displayed a less favorable panorama when compared to literature results.…”
Section: Discussionmentioning
confidence: 95%
“…It has been proposed that Asiatic acid has various pharmacological activities such as anti-inflammatory and antioxidant, as well as the potent anti-hypertensive, neuro and cardio-protective, antimicrobial, and antitumor activities [5]. Many studies had proved the anti-cancer effects in vitro or in vivo of AA in breast cancer, ovary cancer, colon cancer, gastric cancer, cholangiocarcinoma, glioblastoma, lung cancer, lymphoma, and melanoma [6,[11][12][13][14][15][16][17][18]. Our study corresponds with these researches and revealed the anti-cancer effect of AA in both dose and time dependent manners in cisplatin-resistance NPC cell lines (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested in current studies that asiatic acid may become one of the important multitarget drugs from natural sources, which can be used for further drug development and clinical application [21]. In the past few years, asiatic acid has been proved to be a potential anticancer compound, and it has been demonstrated in multiple studies [22][23][24][25] that asiatic acid has an inhibitory effect on cancer of the liver, brain, ovary, and lungs. Specifically, asiatic acid has outstanding advantages in reducing inflammation, caring for the skin, and protecting the liver and nerves.…”
Section: Discussionmentioning
confidence: 99%